Bacterial extracellular vesicles control murine norovirus infection through modulation of antiviral immune responses - Bhar, Sutonuka; Zhao, Guanqi; Bartel, Julia D.; Sterchele, Heather; Del Mazo, Alexa; Emerson, Lisa E.; Edelmann, Mariola J.; Jones, Melissa K. (Frontiers in Immunology, 2022)
Human norovirus is the primary cause of non-bacterial gastroenteritis globally and is the second leading cause of diarrheal deaths in children in developing countries. However, effective therapeutics which prevent or clear norovirus infection are not yet available due to a lack of understanding regarding norovirus pathogenesis. Evidence shows that noroviruses can bind to the surface of commensal bacteria, and the presence of these bacteria alters both acute and persistent murine norovirus infection through the modulation of host immune responses. Interestingly, norovirus-bacterial interactions also affect the bacteria by inducing bacterial stress responses and increasing the production of bacterial extracellular vesicles. Given the established ability of these vesicles to easily cross the intestinal barriers, enter the lamina propria, and modulate host responses, we hypothesized that bacterial extracellular vesicles influence murine norovirus infection through modulation of the antiviral immune response. In this study, we show that murine norovirus can attach to purified bacterial vesicles, facilitating co-inoculation of target cells with both virus and vesicle. Furthermore, we have found that when murine noroviruses and vesicles are used to co-inoculate macrophages, viral infection is reduced compared to virus infection alone. Specifically, co-inoculation with bacterial vesicles results in higher production and release of pro-inflammatory cytokines in response to viral infection. Ultimately, given that murine norovirus infection increases bacterial vesicle production in vivo, these data indicate that bacterial vesicles may serve as a mechanism by which murine norovirus infection is ultimately controlled and limited to a short-term disease.